Efektivitas Permainan Scrabble Ball Terhadap Pengenalan Huruf Anak Di Paud Maghfirah Padang - Mita Sari, Desrilla; Suryana, Dadan; Zulminiati, Zulminiati (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The Knowledge of letters in early childhood is very important to enter the process of learn to read and write. One of them is by using learning media that is suitable with the child's developmental characteristics. This studing aims to finds out,how much effectiveness thes Scrabble Ball games has on The Developments of child letter recognition in the Paud Maghfirah Padang.This research uses a quantitative approach in the form of experimental quasy. The popullation of this study wass all family planning students in Paud Maghfirah Padang with the sampling technique using purposive sampling, namely groups of KB1 and KB2, each consisting of 10 children. Data collection techniques using the test, In the forrm of statement’s of 4 statements and data collection tools used statement sheets. Then the data is processed with a difference test (t-test). Based On data analysis, the average test results obtained from the experimental class were 92.5 and SD was 7.28 while the control class was 82,5 and SD was 6,12. Hypothesis testing obtained tcount of 31,1645 and ttable off 2,56310 at the reaal levels α= 0,05 (5%) with dk of 18. Thens it can be,concluded that the use of Scrabble Ball game is effective for developing children's letter recognition skills in Paud Maghfirah Padang city